Modification of hydrophilic channels in Nafion membranes by DMBA: Mechanism and effects on proton conductivity. Issue 16 (28th June 2014) - Wang, Rujie; Yan, Xiaoming; Wu, Xuemei; He, Gaohong; Du, Lin; Hu, Zhengwen; Tan, Ming
ABSTRACT Modification of proton conductive channels (PCCs) in Nafion has been achieved with the assistance of 3, 4‐dimethylbenzaldehyde (DMBA). During annealing, ionic clusters develop from small isolated spheres (1.72 nm) to wide continuous channels (5.15 nm), and the crystallinity of Nafion/DMBA membranes is also improved from 17% to 32% as shown by X‐ray diffraction. Molecular dynamic simulation reveals that hydrogen bonding and hydrophobic interaction between DMBA and Nafion work synergistically to achieve better phase separation. The morphology–property relationship shows that, versus various PCCs width, the corresponding proton conductivities vary greatly from 0.079 to 0.139 S/cm at 80 °C. By carefully tuning the width of PCCs, the proton conductivity shows an improvement of 22–34% as compared with pristine Nafion. A significant enhancement on the maximum power density is achieved for the membrane electrode assembly on Nafion/DMBA‐8h (as high as 1018 mW/cm−2), yielding an enhancement of 39% on pristine Nafion‐8h (730 mW/cm−2). © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 201452, 1107–1117